2019
DOI: 10.3390/w11091833
|View full text |Cite|
|
Sign up to set email alerts
|

A Comprehensive Modelling Approach to Assess Water Use Efficiencies of Different Irrigation Management Options in Rice Irrigation Districts of Northern Italy

Abstract: European rice production is concentrated in limited areas of a small number of countries. Italy is the largest European producer with over half of the total production grown on an area of 220,000 hectares, predominantly located in northern Italy. The traditional irrigation management (wet seeding and continuous flooding until few weeks before harvest—WFL) requires copious volumes of water. In order to propose effective ‘water-saving’ irrigation alternatives, there is the need to collect site-specific observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…In this Special Issue, there are five papers published in this category. Mayer et al (2019) [4] developed an agro-hydrological modelling framework based on three sub-models (one for the agricultural areas, one for the groundwater zone, and one for the channel network) to investigate the water use efficiency in rice areas of northern Italy at the irrigation district scale. Once calibrated for a district of 1000 ha using meteorological, hydrological and land-use data of a four-year period, the model was used to assess four different irrigation management scenarios: (1) wet seeding and continuous flooding until few weeks before harvest (WFL), (2) dry seeding and delayed flooding (DFL), (3) alternate wetting and drying (WDA), and (4) WFL followed by post-harvest winter flooding (WFL-W).…”
Section: Precision Irrigation Models and Controlsmentioning
confidence: 99%
“…In this Special Issue, there are five papers published in this category. Mayer et al (2019) [4] developed an agro-hydrological modelling framework based on three sub-models (one for the agricultural areas, one for the groundwater zone, and one for the channel network) to investigate the water use efficiency in rice areas of northern Italy at the irrigation district scale. Once calibrated for a district of 1000 ha using meteorological, hydrological and land-use data of a four-year period, the model was used to assess four different irrigation management scenarios: (1) wet seeding and continuous flooding until few weeks before harvest (WFL), (2) dry seeding and delayed flooding (DFL), (3) alternate wetting and drying (WDA), and (4) WFL followed by post-harvest winter flooding (WFL-W).…”
Section: Precision Irrigation Models and Controlsmentioning
confidence: 99%
“…1.1, = 0.6 (Mayer et al, 2019). Rice growth stages (ini, dev, mid, end;Allen et al 1998) were registered by the farmer in the farm diary (site E) or obtained through the processing of ESA-Sentinel2 data (site Z; Facchi et al, 2020).…”
Section: Water Balance Computationmentioning
confidence: 99%
“…Some Authors reported that winter flooding may improve the availability of soil moisture in early spring (Taghavi et al, 2015), which could be useful for crop production. Despite this, Mayer et al (2019) simulated different irrigation management scenarios through a surface water-groundwater modelling tool applied to an irrigation district of 1000 ha in northern Italy, and highlighted that the winter flooding of rice fields adopted in the district was carried out too early in the season (from November 15 th to January 15 th ) to be able to influence soil moisture and groundwater levels at the beginning of the agricultural season (end of April-beginning of May). The Authors hypothesized that winter flooding needs to be more prolonged in order to maintain a higher water table at the beginning of summer, which would allow to increase the irrigation efficiency of rice during the cropping season.…”
mentioning
confidence: 99%
“…Climate change and price unpredictability represent severe challenges for Italian producers and agricultural companies, forced to adapt their production processes to the needs of the globalized world (Mayer et al, 2019). At present, no increase of the rice cultivation area in Italy is expected in the near future, whereas, in contrast, a decrease might probably occur if the rice price goes down, or production is affected by globalization dynamics (Venturini, 2016).…”
Section: The Way Ahead: Dry Cultivation and Organic Ricementioning
confidence: 99%